Towards renewal or oblivion? Prospects for post–2020 cooperation between the European Union and the Africa, Caribbean and Pacific Group - Mario Negre; Niels Keijzer; Brecht Lein; Nicola Tissi (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Following the adoption of the Rome Treaty, the European Union (EU) developed a formal and privileged cooperation framework for its relationship with countries in Africa, the Caribbean and Pacific (ACP). Since 2000 cooperation between the EU and the ACP is governed through the Cotonou Partnership Agreement (CPA), which encompasses three complementary dimensions: political dialogue, economic and trade cooperation, and development cooperation. The changing global context, along with institutional, political and socioeconomic developments in the EU and the ACP, raise questions about whether this approach to cooperation has sufficiently delivered on its objectives, and which evolutions – or revolutions – may be necessary for these regions' future cooperation. This paper seeks to complement existing evidence with the findings of a detailed review of the literature and the perceptions of past, present and future ACP–EU cooperation gathered from a wide range of stakeholders in ten ACP countries.
Keywords: 330